The values of news: advertising and television news - Pereira, Francisco José Costa (2021)
This study intends to understand how television news strategy becomes the major source of the channels incomes, through advertising. The study was divided in two parts: one where we intend to characterise the advertising and another to show the economic model supported in the advertising investment. The main results show us that there exists a clear logic of subordination of the prime-time television programs to the commercial strategies and in special to the news services. These news services have a commercial logic in the Portuguese television. They have a high length, between 60 to 90 minutes, and a high rating. Because of this high rating the news services have three advertising blocks associated to them. These three blocks have a high profit with a high percentage of the revenue in prime-time that contributes significantly to the economic model of the television broadcasters.